DETERMINATION OF THE MASS BALANCE OF HIGH-CARBON FERROCHROME IN A SUBMERGED ARC FURNACE - Kapan, Sinan; Camdali, Unal; Celik, Nevin (Begell House Inc, 2024)
In this study, it is aimed to establish one-day mass balance of the materials entering into and leaving from a submerged arc furnace (SAF) where high-carbon ferrochrome is produced in it. The SAF is used in a plant located in Elazig, Turkey. For this purpose, measurements were taken from the SAF during one month by obtaining the necessary permits from the plant. In addition to these measurements, chemical reactions in the SAF are defined based on the information obtained from the literature and the plant. Chrome ore and rich slag are raw materials for furnace; as auxiliary raw materials, coke, coal, electrode paste, quartzite, and bauxite are fed. The product and the waste coming out of the SAF are high-carbon ferrochrome, slag, flue gas, and fly ash. Samples were taken from each raw material and auxiliary raw materials fed into the SAF and the products, then the chemical composition analysis was carried out by using an X-ray fluorescence (XRF) device. The reactions that take place in the SAF are carbothermic reduction reactions. Metal oxides (Cr2O3, Fe2O3, Al2O3, etc.) react with carbon and are reduced as MO + C = M + CO (M = metal). As a result of this study, the mass amounts of the materials entering into and leaving from the SAF established a balance.
Keywords: high -carbon ferrochrome; mass balance; carbothermic reduction